0541 Effects Of Continuous Positive Airway Pressure On Blood Pressure In Obstructive Sleep Apnea. (12th April 2019) - Javaheri, Sogol; Gottlieb, Daniel J; Quan, Stuart F
Abstract: Introduction: Obstructive sleep apnea is associated with hypertension, and studies have demonstrated a modest reduction in blood pressure with continuous positive airway pressure (CPAP) therapy. We evaluated the effects of CPAP versus sham CPAP on blood pressure as part of a large 6 month randomized clinical trial. Methods: We analyzed data from 1101 participants with obstructive sleep apnea and hypertension from the Apnea Positive Pressure Long-term Efficacy Study, a randomized, sham-controlled double-blinded study designed to assess the impact of CPAP on neurocognition. Participants with AHI greater than or equal to ten were randomly assigned to CPAP or sham CPAP. Blood pressures measured in morning and evening at baseline, 2 months, and 6 months were analyzed using a mixed model repeated measures analysis of variance. Results: The largest magnitude reduction was approximately 2.4 mm Hg in morning mean arterial pressure which occurred at 2 months in the CPAP arm as compared to an approximate 0.5 mm Hg reduction in the sham group (CPAP effect -1.6 mm Hg, p=0.003). At 6 months, the difference between groups was diminished and no longer statistically significant (CPAP effect -0.9 mm Hg, p=0.123). Sensitivity analysis with use of multiple imputation approaches to account for missing data did not change the results. Conclusion: Treatment with CPAP for OSA reduces morning, but not evening blood pressure. The effect was greater after 2 than after 6 months of treatment. Support (If Any): NHLBI